2019
DOI: 10.1002/cnm.3259
|View full text |Cite
|
Sign up to set email alerts
|

The presence of helical flow can suppress areas of disturbed shear in parameterised models of an arteriovenous fistula

Abstract: Areas of disturbed shear that develop following arteriovenous fistula (AVF) creation are believed to trigger the onset of intimal hyperplasia (IH), leading to AVF dysfunction. The presence of helical flow can suppress the flow disturbances that lead to disturbed shear in other areas of the vasculature.However, the relationship between helical flow and disturbed shear remains unevaluated in AVF. In this study, computational fluid dynamics (CFD) is used to evaluate the relationship between geometry, helical flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Wall shear stress gradient and oscillatory shear index may not fully capture the complexity of AVF blood flow. Other hemodynamic parameters, such as relative residence time and helicity-based bulk flow indices, 46 may also be associated with AVF remodeling. Sites of turbulent flow were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Wall shear stress gradient and oscillatory shear index may not fully capture the complexity of AVF blood flow. Other hemodynamic parameters, such as relative residence time and helicity-based bulk flow indices, 46 may also be associated with AVF remodeling. Sites of turbulent flow were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…This outof-plane curvature may increase the flow helicity and reduce development of secondary or disturbed flows with disturbed or low WSS. Cunnane, Cunnane [50] investigated the effect of anastomosis angle on helical flow and area of suppressed shear. They reported that out of plane anastomosis curvature angle can increase the helical flow and reduce distribution of low/oscillating WSS.…”
Section: Discussionmentioning
confidence: 99%
“…Average helicity intensity (h 2 ) quantifies the helical nature of the blood flow. Higher h 2 is considered to be atheroprotective as it stabilizes blood flow [43]. Local normalized helicity (LNH) visualizes the helical flow pattern [44].…”
Section: Hemodynamic Descriptorsmentioning
confidence: 99%